Overview of Total Cholesterol Levels at Productive Age in the Imbanagara Health Center Working Area - Intan Fandini; Undang Ruhimat; Rivana Ariyadi; Rahayu Nirmatul Mutmainah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective: Total cholesterol is the total amount of HDL, LDL, and VLDL cholesterol in each deciliter of blood. Risk factors that can affect total cholesterol levels are age, gender, sleep patterns, genetics, physical activity, and body mass index. This study aims to determine the description of total cholesterol levels in productive age in the Imbanagara Health Center Working Area. Method: This research method is descriptive research with a purposive sampling technique and involves 31 respondents the instrument used is a photometer. This research was conducted in the Imbanagara Health Center working area from May to June 2023. Result: The results showed that the total cholesterol levels of 31 respondents, were 25 people (81%) with normal total cholesterol levels, 5 people (16%) with high threshold total cholesterol levels, and 1 other person (3%) with high total cholesterol levels. Conclusion: It can be concluded that of the 31 respondents in the Imbanagara Health Center work area, the average has normal Total Cholesterol results.